The Universality of Management - Muse, William V. (Academy of Management Journal, 1967)
In a study of 72 social fraternities, the author found that there was a significant positive relationship between the degree to which these organizations used selected managerial practices and the success ranking they achieved. This may lend some credence to the belief that management ?principles? or practices have universal application.